BUDAYA FASHION DI JALANAN DALAM STREET PHOTOGRAPHY - Silviana Tahalea (Universitas Trisakti, 2015)
AbstractFashion is a code that needed a description to understand about the personwho's wearing the dress. Every clothes that's worn by somebody brings a strongmessage about the person wearing the clothes, there for cloting in generallybecoming a way to communicate with the world. Fashion it self by any mean canbe represent by our own preception and prespective. This fashion power issuehas becoming my concern, fashion it self also becoming an identity of a changingof an era. In other conception, fashion can de define as a lifestyle or an identity ofa person in certain situation. Fashion always evolving according to an era in adynamic condition.Street fashion phenomenon become a culture in big cities and it's getting morecommon in everyday life an in fashionably modern life. Street is an interstingcontext of fashion as a place for replacing a studio position for photographer anda catwalk for a fashionista. Fashion image is no longger addresed for aprofesional figure model. Now a days fashion is a daily life setting on today'ssociety everyday life. I'm choosing Jakarta's down town, specially SudirmanStreet, because it was one of the most crowded public space in Jakarta. We couldeasily found bussiness center, economic center to a shopping center inSudirman Street. People from various social background, education, jobs andneeds with a various style of fashion could easily be found in here.AbstrakFesyen adalah sebuah kode yang butuh pendeskripsian untuk mengertitentang orang yang mengenakannya. Setiap pakaian yang dikenakanseseorang membawa pesan yang kuat tentang si pemakainya. Olehkarena itu, pakaian seseorang pada umumnya merupakankomunikasinya dengan dunia luar.The purpose of this study was to document the trend of Street Fashion these daysin Jakarta. From these results it can be concluded that the type of fashion that isin the Sudirman area is adjusting place or in other words the way people identifythemselves is to understand their environment.Fashion sendiri dapat diartikanberbagai macam, sesuai dengan persepsi dan perpektif kita masingmasing.Hal inilah yang menjadi ketertarikan untuk bicara mengenaikekuatan fashion, fashion sendiri dapat diartikan bagian dari identitasperubahan era atau zaman. Dalam konsepsi lain fashion juga dapatdidefinisikan sebagai gaya hidup atau identitas seseorang didalamlingkungannya. Fashion terus berkembang sesuai tuntutan zaman dandalam kondisi yang selalu dinamis.Fenomena street fashion yang semakin membudaya di kota besar dansemakin terlihat didalam keseharian kehidupan modern yang semakinfashionable. Jalan merupakan konteks yang menarik untuk fesyen sebagaitempat untuk menggantikan posisi studio bagi para fotografer dancatwalk bagi para penggemar fesyen. Image fesyen tidak lagi hanyadiperuntukan bagi figur model profesional. Sekarang ini fesyen adalahseting kehidupan sehari-hari masyarakat urban.Tujuan penelitian ini adalah untuk mendokumentasikan trend streetfashion yang sedang berlangsung saat ini di Jakarta. Dari hasil penelitiantersebut dapat diambil kesimpulan bahwa jenis fesyen yang ada dikawasan Sudirman adalah menyesuaikan tempat atau dengan kata laincara masyarakat mengidentifikasi dirinya adalah dengan memahamilingkungannya.